Cognitive and Functional Outcome of Patients with Ischemic Stroke at Dr. Hasan Sadikin Hospital Bandung - Nahrowi, Najmia Shabrina; Ong, Paulus Anam; Adam, Achmad (Althea Medical Journal, 2018)
Background: Stroke is the second leading cause of death and adult disability throughout the world in which the risk of cognitive impairment tripled after stroke. Approximately 30% of the patients experience residual disabilities and over half of patients remain physically dependent following a stroke. This study aimed to describe cognitive and functional outcome of patients with ischemic stroke at Dr. Hasan Sadikin Hospital Bandung.Methods: This retrospective descriptive study used secondary data from medical recordsÂ  (January-December 2013) of patients with ischemic stroke at Dr. Hasan Sadikin Hospital, Bandung, and was conducted from JuneâSeptember 2017. Cognitive outcome was determined by the final score of the Indonesia version of MoCA (MoCA-INA), classified into impaired if the score was <26 and normal if the score was >26.Whereas functional outcome was determined by degradation of Barthel Index (BI), from complete dependence to independence.Â  Data were analyzed, presented in the form of tables.Results: Out of a total of 91 subjects consisting of 46 female (50.55%) and 45 male (49.45%), the result showed 55 subjects (60.44%) had cognitive impairment with memory (75.82%) as the highest prevalence of impaired cognitive domain. The functional outcome was 34 patients (37.37%) had moderate to complete dependence whereas only 13 patients (14.29%) were independent.Conclusions: Cognitive impairment occurs in more than 75% ischemic stroke patients with memory as the most commonly impaired domain and more than one third of ischemic stroke patients still have moderate to complete dependence in activities of daily living (ADL).Â